Pragmatic enrichment: beyond Gricean rational reconstruction – a response to Mandy Simons. Issue 5 (4th July 2017) - Carston, Robyn
Abstract: It has been claimed that pragmatic effects that arise in embedded clauses pose a problem for the Gricean reasoning procedure. I maintain, however, that the real issue these phenomena raise for Grice, as he himself acknowledged, is their violation of his saying/implicating distinction. While these effects can be accounted for by Gricean reasoning, which Mandy Simons clearly demonstrates, there is no way round this latter problem other than a major revision of Grice's notion of 'saying' and hence of the saying/implicating distinction.